2019
DOI: 10.1111/ijsa.12230
|View full text |Cite
|
Sign up to set email alerts
|

Reducing assimilation and contrast effects on selection interview ratings using behaviorally anchored rating scales

Abstract: Performance ratings have been shown to be susceptible to various biases. Two of the most influential biases are assimilation and contrast effects. They denote that ratings are biased either toward (assimilation) or away from (contrast) prior reference assessments. Rigorous rater trainings have proven useful to reduce the latter bias, which, however, are rather time‐consuming. A more parsimonious approach achieving a similar purpose may be to optimize the rating material in order to reduce the tendency of being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Research in psychology has shown how salience impacts attention such that the more something stands out, the greater attention it receives [28,29]. Moreover, research on attention has shown that bias in rating scales may arise through sequencing effects related to the manner in which specific attributes of preceding stimuli contrast with novel stimuli in the context of rating tasks [30]. Within inter-group relations, research has demonstrated that demographic salience such as race and gender can impact how others are perceived and treated.…”
Section: Plos Onementioning
confidence: 99%
“…Research in psychology has shown how salience impacts attention such that the more something stands out, the greater attention it receives [28,29]. Moreover, research on attention has shown that bias in rating scales may arise through sequencing effects related to the manner in which specific attributes of preceding stimuli contrast with novel stimuli in the context of rating tasks [30]. Within inter-group relations, research has demonstrated that demographic salience such as race and gender can impact how others are perceived and treated.…”
Section: Plos Onementioning
confidence: 99%
“…Researchers and practitioners have long sought to improve measurement and the performance ratings accuracy (Adler et al , 2016; Speer et al , 2019). In the individual level, specifically, Lubbe and Nitsche (2019) and Battaglio (2015) point out that one of the performance appraisal primary concerns is the error and bias of raters. Given that all performance appraisals are subject to human involvement, error and bias are constant threats to effective evaluation (Battaglio, 2015; DeNisi and Smith, 2014).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Many managers find the structured interview too rigid or simply not useful (Chen, Tsai, & Hu, 2008;Terpstra & Rozell, 1997). Nevertheless, research consistently shows that increasing the use of structured interview could significantly enhance hiring outcomes (Huffcutt & Arthur, 1994;Lubbe & Nitsche, 2019) and reduce the adverse impact (Huffcutt & Roth, 1998;Williamson, Campion, & Malos, 1997). Indeed, a bad hire can incur a significant financial cost to the organization and have a negative impact on workplace morale and productivity (Dunlop & Lee, 2004;Forbes, 2016).…”
Section: Backg Rou N Dmentioning
confidence: 99%